2013
DOI: 10.1177/1524500413483455
|View full text |Cite
|
Sign up to set email alerts
|

Use of Comforting to Enhance Social Marketing Success

Abstract: Successful behavioral change is the Holy Grail for social marketers. Meta-analysis demonstrates that effect sizes of behavioral change in social marketing campaigns is typically low. The present case study uses 4 years of survey data from an Alabama weight loss and behavioral change campaign to develop an explanation for why some people are more successful in lifestyle change efforts than others. Comforting, a communicative form of prosocial behavior, produced the greatest magnitude of change when tested as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…The comforting scale comprises five specific behaviors that are particularly effective in alleviating others' distress (Bippus, 2001). Forbus and Snyder (2013) successfully modified the items to fit a social marketing context. We modified the items to fit this branding context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The comforting scale comprises five specific behaviors that are particularly effective in alleviating others' distress (Bippus, 2001). Forbus and Snyder (2013) successfully modified the items to fit a social marketing context. We modified the items to fit this branding context.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they cannot relate at all. The past research (Forbus & Snyder, 2013) concluded that individuals who use the relating dimension help distressed others find solutions to the problems causing their distress. The present findings may be in line with that past research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social concepts are not only different from tangible objects but also fundamentally different from intangible services, making the understanding of social marketing content more abstract [ 22 ]. It is often difficult for the marketing subject to accurately and specifically describes the characteristics of its marketing purpose, which brings many difficulties to the promotion of marketing activities, making it difficult to communicate effectively with the target audience [ 23 ]. Therefore, it is necessary to develop a strategy by investigating the key criteria for the success of social marketing activities or campaign.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kataria and Larsen (2009) indicated that an effective and clear message as the influencing instrument of battery collection campaign. Forbus and Snyder (2013) emphasized that social marketer should consider developing messages that encourage target audience to give and receive both support and comfort. Wymer (2010) also concluded that social marketer must spread attractive message to influence individuals to adopt healthy behavior.…”
Section: Social Marketing Key Success Factorsmentioning
confidence: 99%